COMPARISON OF HYPER PRODUCER ASPERGILLUS NIGER CULTURES (IFS-5, IFS-6 AND IFS-17) FOR CITRIC ACID FERMENTATION IN SURFACE CULTURE: Short Communication (Biological Sciences - PJSIR, 2004)
Citric acid fermentation by Aspergillus niger is an aerobic process and the organism needs a fairly high and constant oxygen supply for its growth (Hang 1988; Haq et al 2000). Surface culture technique (SCT) is a conventional method of citric acid production. Most of the pilot plants are using this technique due to low energy consumption and manpower involved (Singh et al 1998). In SCT, the substrate remains stationary and organism form mycelial mat on the surface of medium. The relation between constitution of the fermenta- tion medium and rate of citric acid production has been investigated (Elimer and Ewaryst 1995)